Unloaded plates free vibrations, supported by elastic thin-walled rods - N. Melikulov; А.Otakulov (Research Parks Publishing LLC, 2020)
The paper regarded free vibrations of a plate elastically clamped at edges with thin-walled open profile rods and pivotally supported on edges